1988
DOI: 10.1182/blood.v72.1.340.340
|View full text |Cite
|
Sign up to set email alerts
|

Management of alloimmune thrombocytopenia: antenatal diagnosis and in utero transfusion of maternal platelets

Abstract: Neonatal alloimmune thrombocytopenia (NAIT) can cause severe bleeding in the central nervous system (CNS) and death or severe neurologic sequelae. The expression of the PLA1 antigen is detectable as early as 19 weeks of gestation. Alloimmunization can therefore lead to fetal thrombocytopenia very early in pregnancy. Until recently, we have had no means of detecting and assessing the severity of fetal thrombocytopenia during pregnancy. The level of the maternal antibody is not of a predictable value since 20% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(62 citation statements)
references
References 7 publications
3
58
0
1
Order By: Relevance
“…The use of in utero platelet transfusion immediately before delivery was described in greater detail in a series of nine cases, where FBS was carried out at 21 weeks gestation to confirm the diagnosis of AIT (Kaplan et al, 1988). FBS was repeated at 37 weeks with the administration of an in utero platelet transfusion if the fetal platelet count was <50 · 10 9 /l followed by delivery 6-36 h later.…”
Section: History Of the Development Of Antenatal Management For Aitmentioning
confidence: 99%
“…The use of in utero platelet transfusion immediately before delivery was described in greater detail in a series of nine cases, where FBS was carried out at 21 weeks gestation to confirm the diagnosis of AIT (Kaplan et al, 1988). FBS was repeated at 37 weeks with the administration of an in utero platelet transfusion if the fetal platelet count was <50 · 10 9 /l followed by delivery 6-36 h later.…”
Section: History Of the Development Of Antenatal Management For Aitmentioning
confidence: 99%
“…In subsequent pregnancies at risk the fetus will be at least as severely affected as the previous sibling. Antenatal diagnosis of fetal thrombocytopenia by percutaneous umbilical blood sampling (PUBS) has revealed that severe thrombocytopenia (< 30 × 10 9 /l) may occur as early as 20 weeks of gestation (Kaplan et al, 1988). The reported frequency of spontaneous ICH in utero is about 10%, although the exact incidence is not known nor is the most likely time of occurrence.…”
mentioning
confidence: 99%
“…There is no spontaneous correction of thrombocytopenia during pregnancy. On the contrary, serial fetal platelet counts show that the platelet count falls as gestation progresses (Kaplan et al, 1988). Antenatal management is therefore aimed at maintaining a satisfactory fetal platelet count and preventing the complications of thrombocytopenia.…”
mentioning
confidence: 99%
“…However, the optimal antenatal management to prevent intracranial haemorrhage in utero is currently unclear. One approach is the use of intra-uterine platelet transfusions (Kaplan et al, 1988;Murphy rt al., 1990), but, in the absence of specialist facilities and highly skilled staff, this involves considerable risk to the fetus.…”
mentioning
confidence: 99%